Ceftazidime-avibactam induced renal disorders: past and present - Shi, Yanrong; Wu, Jichao; Mi, Wei; Zhang, Xusheng; Ren, Xiuli; Shen, Chengwu; Lu, Cuicui (Frontiers in Pharmacology, 2024)
With the increasing prevalence of multidrug-resistant Gram-negative bacterial pathogens worldwide, antimicrobial resistance has become a significant public health concern. Ceftazidime-avibactam (CAZ-AVI) exhibited excellent in vitro activity against many carbapenemase-producing pathogens, and was widely used for the treatment of various complicated infections. CAZ-AVI is well tolerated across all dosing regimens, and its associated acute kidney injury (AKI) in phase II/III clinical trials is rare. However, recent real-world studies have demonstrated that CAZ-AVI associated AKI was more frequent in real-world than in phase II and III clinical trials, particularly in patients receiving concomitant nephrotoxic agents, with critically ill patients being at a higher risk. Herein, we reviewed the safety data related to renal impairment of CAZ-AVI, and discussed its pharmacokinetic/pharmacodynamic targets and dosage adjustment in patients with impaired renal function. This review aimed to emphasize the importance for healthcare professionals to be aware of this adverse event of CAZ-AVI and provide practical insights into the dosage optimization in critically ill patients with renal dysfunction.